Optimal dose of tirzepatide for type 2 diabetes mellitus: A meta-analysis and trial sequential analysis - Yu, Yunfeng; Hu, Gang; Yin, Shuang; Yang, Xinyu; Zhou, Manli; Jian, Weixiong (Frontiers in Cardiovascular Medicine, 2022)
Abstract: Objective: The purpose of this study is to evaluate the optimal dose of tirzepatide(TZP) for the treatment of type 2 diabetes mellitus(T2DM) by meta-analysis and trial sequential analysis(TSA). Methods: Clinical trials of TZP for T2DM were obtained by searching 8 databases with a time limit from database creation to May 2022. Mean differences(MD) and 95% confidence intervals(95%CI) were used for continuous variables, and RR and 95%CI were used for dichotomous variables. Revman5.3 and TSA0.9.5.10Beta were respectively used for meta-analysis and TSA. Results: Compared with TZP5mg, meta-analysis showed that TZP10mg significantly reduced glycosylated hemoglobin type A1c(HbA1c)(MD-0.24, 95%CI -0.31~-0.17, P<0.00001), fasting serum glucose(FSG)(MD-5.82, 95%CI -8.35~-3.28, P<0.00001) and weight(MD-2.47, 95%CI-2.95~-1.98, P<0.00001), and TZP15mg significantly reduced HbA1c(MD-0.37, 95%CI-0.44~-0.29, P<0.00001), FSG(MD-8.52, 95%CI -11.07~-5.98, P<0.00001) and weight (MD-4.63, 95%CI-5.45~-3.81, P<0.00001). Compared with TZP10mg, TZP15mg dramatically reduced HbA1c(MD-0.12, 95%CI-0.19~-0.05, P=0.001), FSG(MD-2.73, 95%CI-5.29~-0.17, P=0.04) and weight (MD-2.18, 95%CI-2.67~-1.70, P<0.00001). The TSA indicated that the benefits observed in the current information set were conclusive, except for the FSG of "TZP15mg vs TZP10mg". In terms of safety endpoints, meta-analysis revealed that there was no significant difference in the serious adverse events(AEs), major adverse cardiovascular events-4 (MACE-4), cardiovascular death, hypertension, cancer and hypoglycemic of the three dose groups of TZP. Compared with TZP5mg, TZP10mg increased total adverse events(RR1.06, 95%CI1.01~1.11, P=0.03) and gastrointestinal(GI) AEs(RR1.17, 95%CI1.03~1.33, P=0.02), and TZP15mg increased total AEs(RR1.10, 95%CI1.05~1.15, P=0.0001). There were no significant differences in total AEs and GI AEs for TZP15mg compared to TZP10mg. The TSA demonstrated that the total AEs of "TZP15mg vs TZP5mg" were conclusive. Conclusions: TZP15mg >TZP10mg > TZP5mg in terms of lowering glycemia and reducing weight. TZP 5 mg > TZP10mg = TZP15mg in terms of safety. On this basis, we recommend TZP5mg as the first-choice dose for patients with T2DM to minimize AEs while reducing glycemia and weight. If patients cannot effectively control their glycemia after taking TZP5mg, it is recommended to take TZP15mg directly to achieve the best effect of glycemic reduction. However, most of the included studies have the background of basic medication, the independent efficacy and safety of different doses of TZP still need to be tested.